2017
DOI: 10.15294/komunitas.v9i2.10002
|View full text |Cite
|
Sign up to set email alerts
|

Economic Rationality of Residents Living in the Area Prone to Merapi Volcanic Disaster

Abstract: The research concerned here was to know the economic rationality of residents who dwelled again in their former village after the eruption of Mount Merapi in 2010 and refused to be relocated by the government. A combined research method, namely, a combination between a qualitative method and a quantitative one, was used to uncover the rationality. The qualitative part of the research was conducted first by deciding informants considered knowledgeable about the matter under research. Then the informants were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Additionally, they felt connected with their ancestors. These findings are supported by Napsiah et al (2017), who showed that people who live in Mt. Merapi enjoy the economic blessings of the area, such as fertile land and tourist visits.…”
Section: Introductionsupporting
confidence: 57%
“…Additionally, they felt connected with their ancestors. These findings are supported by Napsiah et al (2017), who showed that people who live in Mt. Merapi enjoy the economic blessings of the area, such as fertile land and tourist visits.…”
Section: Introductionsupporting
confidence: 57%
“…Table 10 displays parameters to estimate resilience among Semeru's population. Results acquired on exposure, hazard knowledge-risk perception and associated variablespreparedness around the volcano are significant when compared with studies of community response to volcanic crises in Indonesia, e.g., at Bromo (Bachri et al, 2015) and Merapi, Java (Dove, 2008;Lavigne et al 2008;Mei et al, 2012;Napsiah et al, 2017), and Sinabung, Sumatra (Andreastuti et al, 2019). The latter study compares the ongoing Sinabung and 2014 Kelud unrest cases to highlight factors that influence a community response at the time of an imminent eruption.…”
Section: From Risk Tolerance To Adaptive Capacity and Resiliencementioning
confidence: 98%
“…For Pangukrejo people, their land is a source of livelihood to build houses and to do economic activities such as raising stock and farming, which are all done on the land. Therefore, even though the land has been devastated by the eruption of Mount Merapi, for them, the land remains useful as a source of livelihood that must be maintained [13,14].…”
Section: Ecological Awarenessmentioning
confidence: 99%
“…There have been many studies of people surviving in disastrous areas, such as the survivors from the eruption of Mount Merapi [9][10][11][12][13][14]. Similar studies on floods in Bangladesh have also been deliberately carried out by several researchers [15][16][17].…”
Section: Introductionmentioning
confidence: 99%